Access to Land for Urban Agriculture in Kampala - Kiguli, Lillian N.; Nuwagaba, Augustus; Mwesigwa, David; Kiguli, Juliet (Urban agriculture magazine, 2003)
Agriculture in Kampala is practised mainly in valley slums where the poor live in informal settlements. Although urban agriculture offers easy access to services and markets, gaining access to land to grow food and rear animals is a challenge for the urban poor